Pregunta
upstudy study bank question image url

\[ \begin{array}{l} =2^{6} \cdot 3^{1} \\ =192 \end{array} \] \[ \begin{array}{l} =\frac{2^{x}(3)}{3.2^{x}} \\ =1 \end{array} \] EXERCISE 1 Simplify the expressions without using a calculator: (1) \( \frac{1}{4} a^{5} b^{12} \times \frac{16}{5} a^{3} b^{2} \) \( 2 \frac{2\left(2 a^{4}\right)^{3}}{16 a^{12}} \) (3) \( \frac{6 a^{4}+9 a^{4}}{5 a^{2}} \) \( 4 \quad \frac{3 a^{3} \times 5 a^{5}}{\left(5 a^{3}\right)^{2}} \) \( 5 p^{x-1} p^{x+1} \) (6) \( -2\left(-4 a^{2}+b^{3}\right)^{2} \) \( 7 \quad 16^{4 x} \div 4^{2 x} \) (8) \( \frac{12^{x+1} \cdot 27^{x-2}}{18^{2 x-1}} \) 9) \( \frac{2^{2010} \times 5^{2011}}{10^{1000}} \) \( 10 \frac{3^{x}+3^{x+1}}{8} \) Negative exponents and the meaning of \( a^{0} \) \( a^{0}=1 \) because \( 5 \div 5=1 \) and \( 5^{1} \div 5^{1}=\frac{5^{1}}{5^{1}}=5^{1-1}=5^{0}=1 \quad \) Using Law 2 For example: \( (2 x)^{0}=1 ; 2 x^{0}=2 \times 1=2 ;(a+b)^{0}=1 \)

Ask by Hodges Bolton. in the United States
Feb 03,2025

Solución de tutoría real

Respuesta verificada por el tutor

Responder

1. \( \frac{4}{5} a^{8} b^{14} \) 2. \( 2 \) 3. \( 3 a^{2} \) 4. \( \frac{3}{5} a^{2} \) 5. \( p^{2x} \) 6. \( -32 a^{4} + 16 a^{2} b^{3} - 2b^{6} \) 7. \( 4^{6x} \) 8. \( \frac{8}{27} \) 9. \( 2^{1010} \cdot 5^{1011} \) 10. \( \frac{3^{x}}{2} \)

Solución

Let's simplify each expression step by step. ### (1) \( \frac{1}{4} a^{5} b^{12} \times \frac{16}{5} a^{3} b^{2} \) First, we can multiply the coefficients and the variables separately: \[ \frac{1}{4} \times \frac{16}{5} = \frac{16}{20} = \frac{4}{5} \] Now for the variables: \[ a^{5} \times a^{3} = a^{5+3} = a^{8} \] \[ b^{12} \times b^{2} = b^{12+2} = b^{14} \] Combining these results, we have: \[ \frac{4}{5} a^{8} b^{14} \] ### (2) \( 2 \frac{2(2 a^{4})^{3}}{16 a^{12}} \) First, simplify the expression inside the parentheses: \[ (2 a^{4})^{3} = 2^{3} (a^{4})^{3} = 8 a^{12} \] Now substitute this back into the expression: \[ 2 \frac{2 \cdot 8 a^{12}}{16 a^{12}} = 2 \frac{16 a^{12}}{16 a^{12}} = 2 \cdot 1 = 2 \] ### (3) \( \frac{6 a^{4}+9 a^{4}}{5 a^{2}} \) Combine the terms in the numerator: \[ 6 a^{4} + 9 a^{4} = 15 a^{4} \] Now simplify: \[ \frac{15 a^{4}}{5 a^{2}} = 3 a^{4-2} = 3 a^{2} \] ### (4) \( \frac{3 a^{3} \times 5 a^{5}}{(5 a^{3})^{2}} \) First, simplify the denominator: \[ (5 a^{3})^{2} = 25 a^{6} \] Now simplify the numerator: \[ 3 a^{3} \times 5 a^{5} = 15 a^{3+5} = 15 a^{8} \] Now combine: \[ \frac{15 a^{8}}{25 a^{6}} = \frac{15}{25} a^{8-6} = \frac{3}{5} a^{2} \] ### (5) \( p^{x-1} p^{x+1} \) Using the property of exponents: \[ p^{(x-1) + (x+1)} = p^{2x} \] ### (6) \( -2\left(-4 a^{2}+b^{3}\right)^{2} \) First, expand the square: \[ (-4 a^{2} + b^{3})^{2} = 16 a^{4} - 8 a^{2} b^{3} + b^{6} \] Now multiply by \(-2\): \[ -2(16 a^{4} - 8 a^{2} b^{3} + b^{6}) = -32 a^{4} + 16 a^{2} b^{3} - 2b^{6} \] ### (7) \( 16^{4 x} \div 4^{2 x} \) Convert to the same base: \[ 16 = 4^{2} \Rightarrow 16^{4x} = (4^{2})^{4x} = 4^{8x} \] Now simplify: \[ \frac{4^{8x}}{4^{2x}} = 4^{8x - 2x} = 4^{6x} \] ### (8) \( \frac{12^{x+1} \cdot 27^{x-2}}{18^{2 x-1}} \) Convert to prime bases: \[ 12 = 2^{2} \cdot 3^{1}, \quad 27 = 3^{3}, \quad 18 = 2^{1} \cdot 3^{2} \] Now express each term: \[ 12^{x+1} = (2^{2} \cdot 3^{1})^{x+1} = 2^{2(x+1)} \cdot 3^{x+1} \] \[ 27^{x-2} = (3^{3})^{x-2} = 3^{3(x-2)} = 3^{3x - 6} \] \[ 18^{2x-1} = (2^{1} \cdot 3^{2})^{2x-1} = 2^{2x-1} \cdot 3^{2(2x-1)} = 2^{2x-1} \cdot 3^{4x-2} \] Now substitute back: \[ \frac{2^{2(x+1)} \cdot 3^{x+1} \cdot 3^{3x-6}}{2^{2x-1} \cdot 3^{4x-2}} = \frac{2^{2x+2} \cdot 3^{4x-5}}{2^{2x-1} \cdot 3^{4x-2}} \] Now simplify: \[ = 2^{(2x+2) - (2x-1)} \cdot 3^{(4x-5) - (4x-2)} = 2^{3} \cdot 3^{-3} = \frac{8}{27} \] ### (9) \( \frac{2^{2010} \times 5^{2011}}{10^{1000}} \) Convert \(10^{1000}\): \[ 10^{1000} = (2 \cdot 5)^{1000} = 2^{1000} \cdot 5^{1000} \] Now simplify: \[ \frac{2^{2010} \cdot 5^{2011}}{2^{1000} \cdot 5^{1000}} = 2^{2010-1000} \cdot 5^{2011-1000} = 2^{1010} \cdot 5^{1011} \] ### (10) \( \frac{3^{x}+3^{x+1}}{8} \) Factor out \(3^{x}\): \[ = \frac{3^{x}(1 + 3)}{8} = \frac{3^{x} \cdot 4}{8} = \frac{3^{x}}{2} \] ### Summary of Results 1. \( \frac{4}{5} a^{8}

Revisado y aprobado por el equipo de tutoría de UpStudy

error msg
Explicar
Simplifique esta solución

Extra Insights

Did you know that the concept of exponents dates back to ancient civilizations? The Egyptians and Babylonians used rudimentary forms of exponentiation to solve problems involving area and volume. Over time, mathematicians developed more formal rules, culminating in the laws of exponents we use today, allowing complex expressions to be simplified cleanly and efficiently. When simplifying expressions, one common pitfall is forgetting the rules for negative exponents. Remember, \( a^{-n} = \frac{1}{a^{n}} \) and treat them carefully. Another mistake is misapplying the laws of exponents while combining like bases—always ensure that you add or subtract exponents correctly! Keeping these in mind can make simplifying expressions feel almost like a party trick!

¡Prueba Premium ahora!
¡Prueba Premium y hazle a Thoth AI preguntas de matemáticas ilimitadas ahora!
Quizas mas tarde Hazte Premium
Estudiar puede ser una verdadera lucha
¿Por qué no estudiarlo en UpStudy?
Seleccione su plan a continuación
Prima

Puedes disfrutar

Empieza ahora
  • Explicaciones paso a paso
  • Tutores expertos en vivo 24/7
  • Número ilimitado de preguntas
  • Sin interrupciones
  • Acceso completo a Respuesta y Solución
  • Acceso completo al chat de PDF, al chat de UpStudy y al chat de navegación
Básico

Totalmente gratis pero limitado

  • Solución limitada
Bienvenido a ¡Estudia ahora!
Inicie sesión para continuar con el recorrido de Thoth AI Chat
Continuar con correo electrónico
O continuar con
Al hacer clic en "Iniciar sesión", acepta nuestros términos y condiciones. Términos de Uso & Política de privacidad